Hubungan Pelayanan Publik terhadap Birokrasi Pemerintah di Kecamatan Panca Rijang Kabupaten Sidenreng Rappang - Sartika Akib (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
Abstract The concept of public service had been at all times subjected to change in accordance with public perception. Providing excellent service was important to be the government’s goal. Excellent service in general could be realized if the quality of public services were also good. This should be specifically recognized by the government of Panca Rijang District in Sidenreng Rappang Regency. Community’s satisfaction was one indicator to acknowledge the quality of public services. The purpose of this study was to determine how public relations services related to the government bureaucracy in Panca Rijang District. This study uses a basic survey research using quantitative-descriptive research type. The sample in this study amounted to 50 people. The data were collected through questionnaires, observations, field interviews, and library research. The results of this study indicated that the public service in Panca Rijang District had a good tangibility at a rate of 68%, responsiveness was good at 64%, reliability was good at 74%, assurance was not appropriate at 66%, and empathy was very friendly at 48%. While from bureaucracy point of view, namely the division of labor was unfair at 62% rate, discipline and supervision wasn’t good at 66%, systematic regulation was good at 70%, position hierarchy was good at 50%, officials tied to a single formal assignment was disagreed by 70%, technical terms was strongly agreed by 68%, and position as a career was strongly agreed by 58%. The influencing factors such as education was good at 56%, working experience was unfavorable at 58%, and infrastructure was also unfavorable at 60%.